2018
DOI: 10.2196/jmir.9211
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Dissemination of Internet-Based Cognitive Behavioral Therapy for Youth Anxiety: Feasibility and Acceptability Study

Abstract: BackgroundInternet-based cognitive behavioral therapy (iCBT) for child and adolescent anxiety has demonstrated efficacy in randomized controlled trials, but it has not yet been examined when disseminated as a public health intervention. If effective, iCBT programs could be a promising first-step, low-intensity intervention that can be easily accessed by young people.ObjectiveThe objective of our study was to examine the feasibility and acceptability of a publicly available online, self-help iCBT program (BRAVE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 26 publications
6
73
0
Order By: Relevance
“…The BRAVE Self-Help program has been described in detail previously (March et al, 2018), as has the therapist-assisted version (March et al, 2009; Spence et al, 2008). The program consists of 10 interactive, Web-based CBT sessions developed for the treatment of specific phobia, generalized anxiety disorder, separation anxiety disorder and social anxiety disorder.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BRAVE Self-Help program has been described in detail previously (March et al, 2018), as has the therapist-assisted version (March et al, 2009; Spence et al, 2008). The program consists of 10 interactive, Web-based CBT sessions developed for the treatment of specific phobia, generalized anxiety disorder, separation anxiety disorder and social anxiety disorder.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, March et al (2018) reported on the outcome of 4425 anxious young people who enrolled in an open-access, ICBT intervention. Results showed that young people who completed at least three treatment sessions tended to show significant reductions in anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of four randomized controlled trials (RCTs) provide evidence of the treatment effects of ICBT for adolescents with anxiety disorders [ 11 - 14 ]; two other studies with adolescent populations have been recently published, but their focus was on establishing feasibility [ 15 , 16 ]. The 9-session program developed by Tillfors et al [ 13 ], which represents the earliest published RCT of ICBT, targeted social fears (namely public speaking) among high school students who met diagnostic criteria for social anxiety disorder.…”
Section: Introductionmentioning
confidence: 99%
“…To date, ICBT or e-Mental Health interventions generally, have not been routinely adopted into healthcare services for children and young people (Wozney et al, 2018), nor are there formalised approaches to such dissemination (Hill et al, 2018). Preliminary support for routine implementation has been reported by Jolstedt et al (2018) and March et al (2018), though very different approaches were utilised. Jolstedt et al (2018) distributed a therapist-supported ICBT program to twenty anxious children and their parents via outpatient clinics in Sweden.…”
Section: Introductionmentioning
confidence: 99%